2011
DOI: 10.1108/17554191111157047
|View full text |Cite
|
Sign up to set email alerts
|

User acceptance of hedonic versus utilitarian social networking web sites

Abstract: Purpose -The technology acceptance model (TAM) was developed by Davies et al. to understand the utilitarian benefits of web sites. In recent times, scholars have extended TAM as theoretical underpinning to understand user acceptance of social networking web sites (SNWs) that were hedonic in nature, which seemed inappropriate. The purpose of this paper is to examine the differences in the user acceptance phenomenon of hedonic versus utilitarian SNWs, and highlight that it is essential to provide justice to vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
(20 reference statements)
0
24
0
2
Order By: Relevance
“…For I-EC, receiving and experiencing new information is rewarding because it provokes positive feelings of interest from engagement, entertainment, or aesthetic pleasure associated with such information [53]. Literature has consistently shown that entertainment seeking and users' desire to initiate and maintain existing interpersonal relationships are the most common internal motivations for engaging in interactions facilitated by SNSs [69,86]. SNSs provide a wide variety of entertainment features, including photo and video sharing and chat rooms [69].…”
Section: I-ec As a Moderator Of The Affective Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…For I-EC, receiving and experiencing new information is rewarding because it provokes positive feelings of interest from engagement, entertainment, or aesthetic pleasure associated with such information [53]. Literature has consistently shown that entertainment seeking and users' desire to initiate and maintain existing interpersonal relationships are the most common internal motivations for engaging in interactions facilitated by SNSs [69,86]. SNSs provide a wide variety of entertainment features, including photo and video sharing and chat rooms [69].…”
Section: I-ec As a Moderator Of The Affective Pathmentioning
confidence: 99%
“…Literature has consistently shown that entertainment seeking and users' desire to initiate and maintain existing interpersonal relationships are the most common internal motivations for engaging in interactions facilitated by SNSs [69,86]. SNSs provide a wide variety of entertainment features, including photo and video sharing and chat rooms [69]. For example, with the click of a button, Facebook users can "like" a message, picture, or hyperlink (to indicate approval), giving users a quick and easy form of social interaction [86].…”
Section: I-ec As a Moderator Of The Affective Pathmentioning
confidence: 99%
“…Yang (2010) found that that utilitarian and hedonic performance expectancy, social influence, and facilitating conditions are critical determinants of US consumers' intentions to use mobile shopping services and that the hedonic or entertainment aspect of mobile shopping services is the most critical driver of US consumers' intentions to use mobile shopping services. Meanwhile, the perceived usefulness emerged as a significant mediator in the case of utilitarian SNWs and perceived enjoyment emerged as a significant mediator in the case of hedonic SNWs user acceptance phenomenon (Pillai & Mukherjee, 2011). Bae & Chang (2012) maintained that the relative advantage has the greatest influence on the purchase intention of smart TV, followed by compatibility, entertainment, web-browsing and n-screen.…”
Section: Hedonic Motivationmentioning
confidence: 99%
“…Hu and Chuang ( [34]) found hedonic value to be one of the 'value components' that had a direct and positive effect on customer loyalty intention toward e-retailer websites. Pillai and Mukherji ( [58]) found that the playfulness aspect in hedonic social networking websites had a significant impact in the user acceptance of such websites. Human computer interaction is a social process in which emotions play a significant role ( [54], [56], [57]).…”
Section: Hedonic and Emotional Interfacesmentioning
confidence: 99%